Rituximab Versus Mycophenolate in the Treatment of Recalcitrant Connective Tissue Disease–Associated Interstitial Lung Disease. Issue 1 (4th December 2020) - Zhu, Lisa; Chung, Melody P.; Gagne, Laurence; Guo, Haiwei H.; Guenther, Zachary; Li, Shufeng; Jacobs, Susan; Morisset, Julie; Mooney, Joshua J.; Raj, Rishi; Chung, Lorinda
Abstract : Objective: Interstitial lung disease (ILD) is a major cause of morbidity and mortality in connective tissue diseases (CTDs). We aimed to assess the effect of rituximab ± mycophenolate mofetil (MMF) compared with MMF on pulmonary function and prednisone dosage in patients with CTD‐related ILD (CTD‐ILD). Methods: This retrospective study included 83 patients from Stanford and Centre Hospitalier de l'Universite de Montreal. Fifteen patients received rituximab ± MMF (rituximab group), and 68 patients received MMF only (control group). Results: Median ILD duration at the start of treatment was longer in the rituximab group at 47 months (range: 4‐170) versus 6.5 months (range: 0‐164) in controls. Forced vital capacity (FVC) decreased by 3.0% (range: 11%‐21%) after treatment in the rituximab group, whereas it increased by 2.0% (range: 14%‐25%) in the control group ( p = 0.025). Diffusing capacity of carbon monoxide (DLCO) decreased by 3.0% (range: 10%‐12%) after treatment in the rituximab group, whereas it increased by 4.5% (range: 30%‐36%) in the control group ( p = 0.046). Mixed model analysis controlling for ILD duration, baseline DLCO, systemic sclerosis, pulmonary hypertension, and prednisone use showed no significant difference in FVC or DLCO between groups at 6 months or 1 year. The average daily prednisone dose score decreased after treatment in the rituximab group, whereas it remained unchanged in the control group ( p = 0.017). Conclusion: Rituximab ± MMF did not significantly change pulmonary function compared with MMF alone, but it did result in a relative decrease in average daily prednisone dose in a population with recalcitrant CTD‐ILD.